Qur'anic worldview and natural science at Islamic secondary education: Ulū’l-albāb integration framework - Hassan, Nur Jannah (2018)
The issue of “integration” is a great concern for the post-colonial Muslim world, stuck in the hegemony of a dichotomous education. This have precipitated into conflicts and disequilibrium in the person, family, society and the environment. The presentation lays down major rationales for integrating the worldview of the Qur'an and natural science. It presents the fundamental premises of the Qur’ān in the pursuit of studying nature, specifically on the notion of “iqra'” of the Qur’ān and of the Cosmos, as manifests in man's relation with Allāh, with himself and humanity, and with the cosmos. The presentation skims upon the worldviews that have brought forth natural science to its status quo, global environmental degradation and crises of humanity today, and scholars’ views on contemporary woes. It proposes an integrated model for the pursuit of natural science based on the Qur'anic notion “ūlū al-albāb” for Islamic secondary education, where certain aspects of natural science undergo a careful but thorough reposition, reinterpretation and reorientation from the framework of, and intimately infused with the worldview of the Qur’ān. Such integration is believed to equip the ummah in addressing the conflicts. It is envisioned that such integration can, in the long run, restore the equilibrium, not just within the Muslim person and the ummah but also for humanity and nature.